Two Subpopulations of Noradrenergic Neurons in the Locus Coeruleus Complex Distinguished by Expression of the Dorsal Neural Tube Marker Pax7 - Plummer, Nicholas W.; Scappini, Erica L.; Smith, Kathleen G.; Tucker, Charles J.; Jensen, Patricia (Frontiers in Neuroanatomy, 2017)
Central noradrenergic neurons, collectively defined by synthesis of the neurotransmitter norepinephrine, are a diverse collection of cells in the hindbrain, differing in their anatomy, physiological and behavioral functions, and susceptibility to disease and environmental insult. To investigate the developmental basis of this heterogeneity, we have used an intersectional genetic fate mapping strategy in mice to study the dorsoventral origins of the En1-derived locus coeruleus (LC) complex which encompasses virtually all of the anatomically defined LC proper, as well as a portion of the A7 and subcoeruleus (SubC) noradrenergic nuclei. We show that the noradrenergic neurons of the LC complex originate in two different territories of the En1 expression domain in the embryonic hindbrain. Consistent with prior studies, we confirm that the majority of the LC proper arises from the alar plate, the dorsal domain of the neural tube, as defined by expression of Pax7Cre. In addition, our analysis shows that a large proportion of the En1-derived A7 and SubC nuclei also originate in the Pax7Cre-defined alar plate. Surprisingly, however, we identify a smaller subpopulation of the LC complex that arises from outside the Pax7Cre expression domain. We characterize the distribution of these neurons within the LC complex, their cell morphology, and their axonal projection pattern. Compared to the broader LC complex, the newly identified Pax7Cre-negative noradrenergic subpopulation has very sparse projections to thalamic nuclei, suggestive of distinct functions. This developmental genetic analysis opens new avenues of investigation into the functional diversity of the LC complex.